If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7m + 9m = 9 Combine like terms: -7m + 9m = 2m 5 + 2m = 9 Solving 5 + 2m = 9 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2m = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 2m = 9 + -5 2m = 9 + -5 Combine like terms: 9 + -5 = 4 2m = 4 Divide each side by '2'. m = 2 Simplifying m = 2
| -3=-6/5(1)+b | | 2x^7=7x | | 4y(y+7)=42 | | 0.3(1+a)=2.1a | | 16/9x=128 | | p(x)=x^5-7x^4-2x^3+78x^2-63x-135 | | 6=(7-2x)(3-2x) | | x^2+5=16 | | 4[-8x+5]=-32x-26 | | 12-(10xn)=-28 | | -5.9a-2/3=5/6 | | -57=-19p | | -5/9-2/3=5/6 | | -6x^2=-24 | | -4x-2=-2x | | -4+4x-x=20 | | 3[1-3x]=2[-4x+7] | | 12-(10xn)=28 | | 29=n-16 | | 8-x/2=53 | | X+9+2x+6=90 | | 4x+4-x=31 | | -26=n-13 | | 1/4x+4=7 | | 3(x+3)=-3(x+1)-5 | | 2d-2+3d=38 | | -5x+18=-8x | | -2x+47=-28 | | 8x+4[4x-3]=4[6x+4]-4 | | 4/3x+2=-2 | | 7x+26=10x+8+15x | | -7x+16=x |